Effect of Vacuum Intrusion Compaction on the Mechanical Properties of Mortar - Chung, K.Y.; Sulieman, M.Z (EDP Sciences, 2014)
The Vacuum Intrusion Compaction Method (VICM) can be defined as a mortar or cement based material compaction method which applies the principle of air pressure in extracting air bubbles trapped in mortar in order to achieve the objective of compaction. This alternative compaction method is able to prevent segregation from happening in mortar and other cement based materials. It also provides better control over the orientation of the elements inside the mortar. Laboratory tests on the physical and mechanical properties of mortars were conducted to study bulk density, porosity, compressive strength, and flexural strength in the early stages of strength development of different mortars. Through such testing, the effectiveness of the vacuum intrusion method on the effect of compaction could be observed. The outcome of this research shows that the VICM is capable of compacting mortar and extracting macro pores, thereby providing a relatively similar compressive strength and flexural strength to that of the standard compaction method. However, it is not efficient in extracting micro pores, therefore, leading to high porosity of the mortar specimens. As a conclusion, the vibration compaction method is still considered a good compaction method when compared to VICM.